1036. Whole Genome Sequencing Analysis of a Large Cohort of Staphylococcus epidermidis Blood Culture Positive Isolates From a Multicenter Clinical Trial. (26th November 2018) - Dib, Rita Wilson; Li, Xiqi; Shelburne, Samuel; Chaftari, Anne-Marie; Hachem, Ray Y; Reitzel, Ruth; Vargas-Cruz, Nylev; Holland, Thomas L; Fowler, Vance G; Raad, Issam
Abstract: Background: Staphylococcus epidermidis is a leading cause of healthcare-associated bacteremia, but the clinical course of S. epidermidis isolated from blood cultures ranges from contamination to serious deep seated infections. We tested the hypothesis that the genetic characteristics of S. epidermidis isolated from blood cultures are significantly associated with disease severity using whole genome sequencing (WGS). Methods: We performed WGS of 163 S. epidermidis isolates from a large prospective multicenter, randomized control trial that assessed the safety and efficacy of algorithm-based treatment of patients with staphylococcal bacteremia (ClinicalTrials.gov #NCT01191840). Patient's infection types were divided into simple (including possible contamination), uncomplicated and complicated bacteremia. Failure was defined as persistent signs and symptoms of infection at 72 hours, persistent bacteremia at 7 days, relapse, complications or overall mortality within 28 days of therapy. WGS was performed using Illumina Miseq, followed by in silico multi-locus sequence type identification and phylogenomic analysis using kSNP. Results: Of the 163 isolates analyzed, 39 sequence types (STs) were identified with ST2 and ST5 isolates being most frequently identified (21% and 20%, respectively). ST2 and ST5 isolates were significantly more likely associated with uncomplicated and complicated infections rather than simple bacteremia ( P = 0.01 by χ 2 test). By multivariate regression analysis, having an ST2 or ST5 S. epidermidis bacteremia was an independent predictor of a complicated infection (odds ratio 4.28, 95% CI 1.36–13.42). Using WGS based branching points rather than sequence typing allowed for additional strengthening of the association of S. epidermidis genetic clustering and clinical infection types (figure). Although there was no significant difference in failure rates among patients infected with different STs, ST2/ST5 strains were significantly more likely to cause relapsing infections (85.7%, P = 0.02). Conclusion: WGS could offer a prognostic tool in the management of S. epidermidis bacteremia. ST2 and ST5 strains may help predict a complicated bacteremia course which would warrant appropriate antimicrobial therapy. Disclosures: T. L. Holland, Basilea: Consultant, Consulting fee. Motif Bio: Consultant and Scientific Advisor, Consulting fee. Theravance: Consultant, Speaker honorarium. Genentech: Consultant, Consulting fee. V. G. Fowler Jr., Debiopharm: Consultant, Consulting fee. Durata: Consultant, Consulting fee. Merck: Consultant and Scientific Advisor, Consulting fee. Cerexa/Actavis/Allergan: Grant Investigator, Grant recipient. Pfizer: Consultant and Grant Investigator, Consulting fee and Grant recipient. Advanced Liquid Logics: Grant Investigator, Grant recipient. NIH: Grant Investigator, Grant recipient. MedImmune: Consultant and Grant Investigator, Consulting fee and Grant recipient. Basilea: Consultant and Grant Investigator, Consulting fee and Grant recipient. Karius: Grant Investigator, Grant recipient. Contrafect: Consultant and Grant Investigator, Consulting fee and Grant recipient. Regeneron: Grant Investigator, Grant recipient. Genentech: Consultant and Grant Investigator, Consulting fee and Grant recipient. Affinergy: Consultant and Grant Investigator, Consulting fee and Grant recipient. Locus: Grant Investigator, Grant recipient. Medical Surface, Inc.: Grant Investigator, Grant recipient. Theravance: Consultant, Consulting fee and Speaker honorarium. Green Cross: Consultant, Speaker honorarium. Grifols: Consultant, Consulting fee. xBiotech: Consultant, Consulting fee. Achaogen: Consultant, Consulting fee. Medicines Co: Consultant, Consulting fee. Novartis: Consultant, Consulting fee. Novadigm: Consultant, Consulting fee. Bayer: Consultant, Consulting fee. Cubist: Consultant, Consulting fee. Debiopharm: Consultant, Consulting fee. Durata: Consultant, Consulting fee. I. Raad, The University of Texas MD Anderson Cancer Center: Shareholder, Licensing agreement or royalty. The Unversity of Texas MD Anderson Cancer Center: Shareholder, Dr. Raad is a co-inventor of the Nitroglycerin-Citrate-Ethanol catheter lock solution technology which is owned by the University of Texas MD Anderson Cancer Center (UTMDACC) and has been licensed to Novel Anti-Infective Technologies LLC, in which UTMDACC and Licensing agreement or royalty.